47 Arni 'terminates' traditional heart failure treatment. (October 2018) - O'Connor, C; Kumar, J; Caples, N; Cronin, E; Asgedom, S; O'Callaghan, P; Owens, P
Abstract : Background: Heart failure is one of the leading causes of morbidity and mortality in cardiovascular patients. This places significant burden on the health service in Ireland- accounting for 7% of all HSE inpatient bed days. The PARADIGM-HF trial introduced Sacubitril/Valsartan which belongs to a novel class of medication, the Angiotensin Receptor Neprilysin Inhibitor (ARNI). The results of the PARADIGM-HF trial were such that treatment with Sucubitril/Valsartan has been adopted by both the ESC and the AHA guidelines as a class I recommendation for heart failure with reduced ejection fraction (HFrEF). Aims: The purpose of the study was to determine if initiation of treatment with sacubitril/valsartan led to an improvement in clinical outcome in the following domains: Improvement in echo derived ejection fraction; Reduction in hospitalisations with heart failure; Improvement in NYHA functional class. Methods: Retrospective and prospective cohort analysis was performed in all patients with HFrEF and who have completed follow-up whilst on ARNI treatment 'ARNI group'. This was compared with matched controls who received traditional heart failure treatment 'traditional treatment group'. We reviewed echo reports and NYHA class of patients, as determined by experienced heart failure nursing staff, to determine any improvement in functional capacity and left ventricular ejection fraction (LVEF). Additionally, hospital in-patient enquiry (HIPE) dataset was used to determine the number of admissions to hospital with heart failure 6 months prior and 6 months after commencing sacubitril/valsartan in our cohort. Results: We enrolled 26 patients with sufficient follow-up data for the 'ARNI group' (16 male and 10 female), and compared these patients with 20 patients (13 male and 7 female) who received traditional treatment for heart failure (average ages 68 vs 73 respectively p=0.22, initial LVEF 20.89% vs 21.35% respectively). Comparing the groups post treatment, the ARNI group was associated with an increase from 20.89% to 34.21% (Wilcoxon rank sum p≤0.0001) whereas the traditional treatment group has an associated increase from 22.75% to 27%. The ARNI group had a significantly superior improvement in LVEF when compared with traditional treatment (12.9% vs 4.25% Mann Whitney U p=0.01314). Complete admission data was available for 19 patients. A total of Admission rates fell from an average of 30 in the 6 months prior to initiation of treatment, to 9 in the six months after (p<0.02, Wilcoxon Rank sum test). The NYHA class fell in 24/26 subjects from pre to post treatment (p<0.0001, Sign test), and fell by a median of 1 NYHA functional class. Conclusion: Treatment with ARNI in this cohort was associated with significantly improved LVEF, hospital admission rates and NYHA functional class.